(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Introduction: Neural tube defects (NTDs) are a global disease, with the largest burden falling to low-and middle-income countries. Proper management of affected children can lead to a meaningful and productive life, and poorly managed cases of NTDs can be a devastating obstacle not only for patient but also for the patient’s family. Methodology: This prospective observational study was conducted in the Department of Paediatric Surgery, Sylhet M.A.G. Osmani Medical College & Hospital during the period from March, 2018 to August, 2020. Thirty children with a neural tube defect during the study period were included. Associated with life threatening major congenital malformations were excluded. The surgical management protocol used for different sites of NTDs was studied. Results: The ages of the patients ranged from 1 day to 9 years with the median age of 3.5 days. The types of NTDs were myelomeningocele (73.3%), encephalocele (10.0%), lipomeningocele (10.0%) and meningocele (6.7%). The nature of neural tube defects was ruptured in (60.0%) and not ruptured in (40.0%). Associated birth defects in this study were hydrocephalus in 56.7%, club foot in 16.7%, cervical prolapse in 6.7% and kyphosis in 6.7% cases. Associated neurological defects were lower limb paresis and paralysis in 83.3%, Urinary incontinence in 50.0% and faecal incontinence abnormality in 40.0% of cases. Postoperative complications were wound infection in 10.0%, wound dehiscence in 16.7%, CSF leakage in 23.3% and meningitis in 10.0% cases. The overall mortality rate was 6.7% of cases. Outcome of this study was recovery without complication in 66.7%, recovery with complications in 26.7% and death in6.7% of cases. Recovery without complication was more frequent than recovery with complications and death. Conclusion: There was recovery without complication in most cases after operation. Early operation is associated with recovery without complication. Journal of Paediatric Surgeons of Bangladesh (2023) Vol. 14 (1 & 2): 11-16